RANDOM VIBRATION FATIGUE ANALYSIS AND STRUCTURAL DESIGN IMPROVEMENT OF BATTERY PACK BASED ON AN VEHICLE - DAI JiangLiang; XIONG Fei; LIU Jing; CHEN Chen; CHEN Hu; YANG YueDong (Jixie qiangdu, 2020)
Based on random vibration theory and fatigue analysis method in frequency domain,with finite element software to construct the battery pack failure model of random vibration fatigue analysis and to calculate the fatigue life of the structure,the analysis results are in good agreement with the test results. Analyze the failure mechanism of the structure and carry out structural design improvement,the simulation and test results show that the fatigue life of the improvement scheme is significantly improved,and it has better anti vibration durability.